Investigation of pollution flashover on high voltage insulators using artificial neural network - Gencoglu, M. T.; Cebeci, M. (Pergamon-Elsevier Science Ltd, 2009)
High voltage insulators form an essential part of the high voltage electric power transmission systems. Any failure in the satisfactory performance of high voltage insulators will result in considerable loss of capital, as there are numerous industries that depend upon the availability of an uninterrupted power supply. The importance of the research on insulator pollution has been increased considerably with the rise of the voltage of transmission lines. In order to determine the flashover behavior of polluted high voltage insulators and to identify to physical mechanisms that govern this phenomenon, the researchers have been brought to establish a modeling. Artificial neural networks (ANN) have been used by various researches for modeling and predictions in the field of energy engineering systems. In this study, model of V-C= f (H,D,L,sigma,n,d) based on ANN which compute flashover voltage of the insulators were performed. This model consider height (H), diameter (D). total leakage length (L), surface conductivity (sigma) and number of shed (d) of an insulator and number of chain (n) on the insulator. Crown Copyright (C) 2008 Published by Elsevier Ltd. All rights reserved.
Keywords: Pollution flashover; Flashover voltage; Artificial neural networks